Revue Faire 46 - 50. - Langdon, James; Niessen, Richard; Chancogne, Thierry; Kritis, Joris; Pageard, Camille; Renaud, Simon (Paris : Empire Editions, 2024)
verzameling van 15 nummers van het tijdschrift Revue Faire : n°46 — A calculated approach: Norm’s unreasonable reasonableness. Author: James Langdon (November 2024) n°47 & 48 — Mechanical translations: — Machines, Accents, and Affects. Author: Camille Pageard (December 2024) — Electric Letters. Author: Simon Renaud (December 2024) n°49 — Lawrence Weiner: We Are Ships at Sea, Not Ducks On a Pond. Author: Joris Kritis + interviews with Nora Turato & Linda van Deursen (January 2025) n°50 — A Site: The Palace of Typographic Masonry. Author Thierry Chancogne (February 2025) n°51 — Paper ruins, future routes: International Library of Fashion Research. Author: Aude Fellay (March 2025) n°52 — A Mode of Representation: 3D. Authors: Manon Bruet + illustrations by Harriet Davey (April 2025) n°53 — Photobook: The New Face of Photophilia. Author: Clément Chéroux + book selection with Théophile Calot (May 2025) n°54 — Art direction in Art. Author: Michela Zoppi & Rory McGrath (end of 2025) n°55 — Matrix font. Author: Simon Renaud (end of 2025) n°56 — Graphic Designers as Iconographers. Author: Thierry Chancogne (end of 2025) n°57 — Pontus Hulten. Author: Malou Messien (end of 2025)
boek